Can water, energy, and food policies in support of solar irrigation enable gender transformative changes? Evidence from policy analysis in Bangladesh and Nepal - Khadka, Manohara; Uprety, Labisha; Shrestha, Gitta; Shakya, Shristi; Mitra, Archisman; Mukherji, Aditi (Frontiers Media, 2024)
Solar irrigation pumps (SIPs) are emerging as a popular technology to address water, energy, and climate change challenges in South Asia while enhancing livelihoods and food security. SIPs are deemed to be a women-friendly renewable energy technology (RET) due to their design, operating system, and safety. While the gender dimensions of natural resources are well documented, the extent to which the water, energy, and food (WEF) policies—including policies to promote SIP technologies in the countries of South Asia—conceptualize and operationalize gender equality and social inclusion (GESI) is not well understood. Therefore, in this study, we reviewed 39 WEF sectoral policies of Bangladesh and Nepal by adopting a gender-transformative analysis approach to rank the policies on a continuum ranging from a scale of 0–3 (denoting gender-unaware, gender-aware, gender-responsive, and gendertransformative). We found that the governments in both countries commit to gender equality and women’s advancement in their WEF sector policies, institutions, and decision-making by ensuring gender and justice principles in their constitutions and national development frameworks. However, these higher-level aspirational principles are not always operationalized in the WEF sector policies. We found that the WEF policies are aware of the need to include GESI and social equity in sectoral programming, yet operational rules for their implementation often fail to challenge structural barriers. Such barriers hinder women and marginalized groups from participating in and benefiting from WEF policies, including the deployment of SIP technologies. This calls for a transformation not only in project implementation but also in the policymaking processes of WEF sectors in the South Asian region.